Supporting Student Skill Development to Enable the Use of Networks for Collaborative Learning - Jenkins, Martin; Bailey, Lynnette (Proceedings of the International Conference on Networked Learning, 1998)
This case study examines the provision of scaffolding when using network technologies to support the delivery of an Information Skills module. ’Information Skills for Independent Learning’, a second year module, was run for the first time during the academic year 1997-98. This module, open to students from al! backgrounds, aims to develop students’ information skills in the context of a rapidly changing information society. The students from different campuses, disciplines, and various modes of attendance, presented a diverse range of skills. Delivery was ’off-line’ using a practical, hands-on approach with emphasis on student collaboration and discussion. The use of networked information sources was obviously a major component of the course. More importantly the module is underpinned by concepts of information retrieval that can be applied to any learning situation.